PRELIMINARY PHYTOCHEMICAL STUDIES ON SOLANUM SURATTENSE BURM.F. SEEDS - Shahiladevi, S. (Medknow Publications & Media Pvt Ltd, 2006)
Solanum surattense Burm.f. has been largely used in the indigenous system of medicine. A preliminary pharmacognostical study of the seed has been undertaken and the physico-chemical, fluorescent and qualitative phytochemical tests have been worked out and the results were presented.